2011
DOI: 10.7863/jum.2011.30.4.517
|View full text |Cite
|
Sign up to set email alerts
|

Telesonography: Foundations and Future Directions

Abstract: The practice of telesonography has yielded promising results in several domestic and international projects aimed at providing basic sonography services. Common themes that recur within telesonography-based research include the quality of transmitted images, clinical applications, and technical and nontechnical barriers to implementation. The research base continues to grow in concert with expanding telecommunications capabilities and refinement of small portable sonographic devices. Persistent barriers to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…this result corresponds with the findings reported by latalski et al, who demonstrated that GPs perceive their knowledge and skills as inadequate, and thus they often need help from more experienced colleagues [11]. Persistent barriers to the deployment of telesonography systems include a lack of telecommunications access, a lack of standard training and operational protocols and a scarcity of research regarding the long-term health impact of telesonography within target communities [28]. to enable family physicians to consult online, it is necessary to develop a teleinformatic infrastructure for the entire health care system.…”
Section: Imaging Problemssupporting
confidence: 85%
“…this result corresponds with the findings reported by latalski et al, who demonstrated that GPs perceive their knowledge and skills as inadequate, and thus they often need help from more experienced colleagues [11]. Persistent barriers to the deployment of telesonography systems include a lack of telecommunications access, a lack of standard training and operational protocols and a scarcity of research regarding the long-term health impact of telesonography within target communities [28]. to enable family physicians to consult online, it is necessary to develop a teleinformatic infrastructure for the entire health care system.…”
Section: Imaging Problemssupporting
confidence: 85%
“…Among the different areas of teleradiology, teleultrasonography is potentially the safest and least expensive area because it does not utilize ionizing radiation and is affordable [3, 4]. Investigators in the United States, the United Kingdom, Canada, and Australia were the pioneers in this research and in carrying out pilot studies [5–9].…”
Section: Historical Perspectivesmentioning
confidence: 99%
“…Within these two categories of research, there are three recurring themes that are relevant to the successful implementation of a teleultrasonography system: (a) the quality of the transmitted images; (b) clinical applications; (c) the nontechnical and technical barriers to implementation [4]. …”
Section: Research Categories and Themesmentioning
confidence: 99%
See 2 more Smart Citations